Intratracheally Inhalable Nifedipine-Loaded Chitosan-PLGA Nanocomposites as a Promising Nanoplatform for Lung Targeting: Snowballed Protection via Regulation of TGF-β/β-Catenin Pathway in Bleomycin-Induced Pulmonary Fibrosis - Mohammed H. Elkomy; Rasha A. Khallaf; Mohamed O. Mahmoud; Raghda R. S. Hussein; Asmaa M. El-Kalaawy; Abdel-Razik H.; Heba M. Aboud (MDPI AG, 2021)
Pulmonary fibrosis is a serious ailment that may progress to lung remodeling and demolition, where the key participants in its incidence are fibroblasts responding to growth factors and cellular calcium swinging. Calcium channel blockers, like nifedipine (NFD), may represent auspicious agents in pulmonary fibrosis treatment. Unfortunately, NFD bears complicated pharmacodynamics and a diminished systemic bioavailability. Thus, the current study aimed to develop a novel, non-invasive nanoplatform for NFD for direct/effective pulmonary targeting via intratracheal instillation. A modified solvent emulsification-evaporation method was adopted for the fabrication of NFD-nanocomposites, integrating poly(D,L-lactide-co-glycolide) (PLGA), chitosan (CTS), and polyvinyl alcohol, and optimized for different physiochemical properties according to the 32 full factorial design. Additionally, the aerodynamic behavior of the nanocomposites was scrutinized through cascade impaction. Moreover, the pharmacokinetic investigations were conducted in rats. Furthermore, the optimum formulation was tested in bleomycin-induced pulmonary fibrosis in rats, wherein fibrotic and oxidative stress parameters were measured. The optimum nanocomposites disclosed a nanosized spherical morphology (226.46 nm), a high entrapment efficiency (61.81%) and a sustained release profile over 24 h (50.4%). As well, it displayed a boosted in vitro lung deposition performance with a mass median aerodynamic diameter of 1.12 µm. Pharmacokinetic studies manifested snowballed bioavailability of the optimal nanocomposites by 3.68- and 2.36-fold compared to both the oral and intratracheal suspensions, respectively. The intratracheal nanocomposites revealed a significant reduction in lung fibrotic and oxidative stress markers notably analogous to normal control besides repairing abnormality in TGF-β/β-catenin pathway. Our results conferred a compelling proof-of-principle that NFD-CTS-PLGA nanocomposites can function as a promising nanoparadigm for pulmonary fibrosis management.